Microbial CH4 and N2O Consumption in Acidic Wetlands - Kolb, Steffen; Horn, Marcus A. (Frontiers in Microbiology, 2012)
Acidic wetlands are global sources of the atmospheric greenhouse gases methane (CH4), and nitrous oxide (N2O). Consumption of both atmospheric gases has been observed in various acidic wetlands, but information on the microbial mechanisms underlying these phenomena is scarce. A substantial amount of CH4 is consumed in sub soil by aerobic methanotrophs at anoxic–oxic interfaces (e.g., tissues of Sphagnum mosses, rhizosphere of vascular plant roots). Methylocystis-related species are likely candidates that are involved in the consumption of atmospheric CH4 in acidic wetlands. Oxygen availability regulates the activity of methanotrophs of acidic wetlands. Other parameters impacting on the methanotroph-mediated CH4 consumption have not been systematically evaluated. N2O is produced and consumed by microbial denitrification, thus rendering acidic wetlands as temporary sources or sinks for N2O. Denitrifier communities in such ecosystems are diverse, and largely uncultured and/or new, and environmental factors that control their consumption activity are unresolved. Analyses of the composition of N2O reductase genes in acidic wetlands suggest that acid-tolerant Proteobacteria have the potential to mediate N2O consumption in such soils. Thus, the fragmented current state of knowledge raises open questions concerning methanotrophs and dentrifiers that consume atmospheric CH4 and N2O in acidic wetlands.